(untitled) (Damascus University Journal of agriculture sciences, 2026)
The study aimed to analyze and study the economics of nurseries that produce apple tree seedlings. The research was carried out in the areas of the Damascus countryside governorate using a comprehensive survey of the study sample. The number of private sector nurseries reached 31 nurseries, of which 12 nurseries produced apple seedlings. The research objectives were reached based on a cost study. College of nursery production, economic returns, and a study of economic efficiency that includes technical and specialized, to determine the optimal degree of efficiency of apple seedlings produced in nurseries. The results of the analysis showed that nurseries producing apple seedlings achieved revenues amounting to (68,609) thousand/SYP, and also achieved a net profit. It amounted to (35,840) thousand, and the cost of one apple planting was (3024.9) SP/planting. These costs include all agricultural operations to obtain an apple planting ready for marketing. The economic efficiency (EE) of the apple plantings produced reached (62%) and the technical efficiency (TE). in order to develop methods for estimating farm efficiency, which amounted to (59%), while the specialized (price) efficiency amounted to (56%), which is higher than technical efficiency. The research reached a set of recommendations for expanding the production of apple seedlings with the desired varieties and origins and establishing mother farms. To reach optimal production efficiency, use production inputs optimally to achieve technical and economic efficiency, and invest in the field of apple seedling production since this activity achieves economic profit. The results showed that the most prominent difficulties and problems facing the owners of nurseries producing apple tree seedlings, which hinder the production of large quantities of apple seedlings at reasonable prices, are the high prices of production requirements as a result of the unavailability of these materials in quantities that meet the needs, and the sale of seedlings at low and unguaranteed prices. Insufficient availability of water and fuel.